Experimental investigation of CIP and PC beam-to-CECFST column joints with simple connection details under lateral cyclic loading - Ma, You-Xin (2022)
Due to the excellent structural performance of Concrete-encased concrete-filled steel tube (CECFST) columns, they have been applied in real practice for several years. In addition, precast technology can be utilised in the construction of CECFST composite structures to further improve productivity. To investigate the behaviour of precast concrete (PC) and cast-in-place (CIP) beam-to-CECFST column joints, a total of 6 joint specimens, including 4 PC and 2 CIP specimens, were thus experimentally studied under lateral cyclic loading. In this paper, the main studied parameters included connection details, construction methods and existence of column axial load. The ultimate strength, failure mode, crack patterns and hysteretic performance of each specimen were analysed in detail. According to the test results, the performance of CIP and PC joint specimens were discussed in the aspect of energy dissipation, ductility and damping coefficients, strength and rigidity degradations. It was found that the PC specimens exhibited comparable cyclic behaviour to the CIP specimens in regards to the maximum strength, hysteretic performance and failure mode. Moreover, based on the measured shear strains, contributions of joint shear resistance from steel tube, inner and outer concrete were quantitatively investigated. Thereafter, the development of shear stress in the outer concrete was compared with the nominal concrete shear strengths from American and European design provisions.